Effect of Digital Literacy on Students Learning Behaviour at Secondary School Level - Nayazi, Nazia; Abbas , Qaisar (Inverge Journal of Social Sciences, 2025)
The COVID-19 pandemic has been a boost to the use of digital learning in secondary schools across the globe, although there is scanty empirical evidence about the effectiveness of digital literacy on the learning behaviour of students in the Pakistani context. The report addresses the correlation between digital literacy and learning behaviour among 542 (Grades 8-10) secondary school students in both the public and the private schools in the major Pakistani cities. The study adopts a mixed-method design by using quantitative surveys and qualitative interviews to explore the effects of digital literacy levels on students in terms of learning motivation, self-efficacy, self-regulated learning, and academic engagement. Structural equation modelling (SEM) was used to test the hypothesized model, with some qualitative analysis being performed with the help of thematic coding. Digital literacy positively influences learning motivation (b = 0.65, p < 0.001) and self-efficacy (b = 0.70, p < 0.001), and academic achievement via improved self-regulated learning (r = 0.72, p < 0.05). The teacher's digital literacy became a critical moderator, and it affected the capacity of the students to critically analyse digital information and to collaborate online in a positive manner. Nonetheless, there are great differences between urban and rural learners in digital literacy skills. The research outlines the major obstacles, such as poor infrastructure, poor teacher education, and unequal access to digital resources. Educational implications include the need to include digital literacy in the regular curriculum, the need to create a detailed teacher professional development initiative, and the need to make sure that all schools in Pakistan have equal technological infrastructure. The study adds to the comprehension of the multifaceted nature of digital literacy in the development of current learning behaviours and presents evidence-based policy and practice suggestions in the field of Pakistani secondary education. References Aksela, O., Lms, J., & Järvelä, S. (2024). Secondary school students’ enacted self-regulated learning strategies in a computer-based writing task: Insights from digital trace data and interviews. Technology, Knowledge and Learning. https://doi.org/10.1007/s10758-024-09789-4 Ashiq, M., Hira, A., & Saeed, A. (2025). The relationship between information literacy and academic performance: A meta-analysis study. Performance Measurement and Metrics. https://doi.org/10.1108/pmm-04-2025-0020 Dada, K. S. J. (2025). Utilization of library technology services for academic performance of senior secondary school students in Zaria Local Government Area, Kaduna State. Journal of Information Systems and Technology. https://doi.org/10.64845/jistech.v1i2.57 Ding, S., Zhang, Y., Huang, H., Chen, D.-F., & Gao, Z. (2024). The relationship between digital literacy and K–12 students’ academic performance: Mediation effects of problem-solving ability. In Proceedings of the International Symposium on Electronics and Telecommunications. https://doi.org/10.1109/ISET61814.2024.00034 Ha, J. H., & Choi, E. J. (2025). The influence of nursing students’ digital literacy on academic achievement in a blended learning environment: Parallel multiple mediation effects of learning presence. The Journal of Korean Academic Society of Nursing Education. https://doi.org/10.5977/jkasne.2025.31.4.452 Hassan, M., Malik, A., Sang, G., Rizwan, M., Mushtaque, I., & Naveed, S. (2022). Examining the parenting style effect on the academic achievement orientation of secondary school students: The moderating role of digital literacy. Frontiers in Psychology, 13, 1063682. https://doi.org/10.3389/fpsyg.2022.1063682 Jan, S. (2018). Gender-, school-, and class-wise differences in the level of digital literacy among secondary school students in Pakistan. Issues and Trends in Educational Technology, 6(2). https://doi.org/10.2458/AZU_ITET_V6I2_JAN Javed, S., Fahad, I., Azhar, E., Syed, M., Ahmed, O., & Zafar, F. (2025). Bridging learning and technology: How digital platforms impact academic performance. Journal for Social Science Archives. https://doi.org/10.59075/jssa.v3i1.154 Jiang, Z., Zhang, Y., Chen, D., Yu, L., & Li, T. (2025, June). The impact of family cultural capital on digital literacy among secondary school students: Chain mediation based on problem-solving ability and learning anxiety. In Proceedings of the 2025 International Conference on Distance Education and Learning (ICDEL) (pp. 573–577). IEEE. https://doi.org/10.1109/ICDEL65868.2025.11193647 Khan, B., Shamsdin, Kubra, Asif, M., & Jabeen, N. (2025). Cyberbullying and its psychological effects on secondary school students in urban Pakistan. Journal of Social Sciences Review, 5(1), 189–196. https://doi.org/10.54183/jssr.v5i1.483 Li, F., Cheng, L., Wang, X., Shen, L., Ma, Y., & Islam, A. (2025). The causal relationship between digital literacy and students’ academic achievement: A meta-analysis. Humanities and Social Sciences Communications. https://doi.org/10.1057/s41599-025-04399-6 Majeed, M. K., & Ahmad, T. B. T. (2024). The impact of digital literacy skills and ICT self-efficacy on academic and functional skills at secondary Islamic schools in District Kot Addu, South Pakistan. Exploresearch. https://doi.org/10.62823/exre/01/03.11 Mudasir, M., & Noor, A. F. (2025). The impact of Chromebook integration on student engagement and learning outcomes in a rural junior high school: A case study at Junior High School Satap 4 Sematu Jaya. International Journal of Universal Education, 3(1). https://doi.org/10.33084/ijue.v3i1.10552 Munawaroh, R., Noviani, E., Sudarmiatin, S., & Zanky, N. (2025). The effect of digital literacy on learning outcomes and 21st-century skills of high school students: A systematic literature review. Global Management: International Journal of Management Science and Entrepreneurship. https://doi.org/10.70062/globalmanagement.v2i4.409 Nacaroğlu, O., Kızkapan, O., & Demir, H. (2025). Middle school students’ motivations and learning competencies in science: Mediating role of digital literacy. Psychology in the Schools, 62(5), 1475–1487. https://doi.org/10.1002/pits.23400 Rafiq-uz-Zaman, M. (2023). The impact of digital literacy on students’ learning outcomes: A comprehensive review. Inverge Journal of Social Sciences, 2(2), 194–205. https://doi.org/10.63544/ijss.v2i2.210 Rahman, A., Al-Qasri, S., & Ofara, W. (2023). Exploring digital literacy practices in English language learning for secondary level students. Journal of Languages and Language Teaching, 11(4). https://doi.org/10.33394/jollt.v11i4.8939 Ramadan, M., Baba, K., Hammad, S., Rustaminezhad, M. A., & Risnawati. (2024). The impact of augmented reality-based learning media on students’ digital literacy skills: A study on junior high school students. Journal of Educational Technology and Learning Creativity, 2(1). https://doi.org/10.37251/jetlc.v2i1.1415 Rezai, M., Vahhab, Z., Izadi, F., & Jahanbani, F. (2024). Examining the mediating role of digital self-efficacy in the relationship between academic self-concept and academic performance of students. Journal of Adolescent and Youth Psychological Studies. https://doi.org/10.61838/kman.jayps.5.10.6 Shuhidan, S. M., Yahaya, W. A. W., Hashim, H., & Baharudin, M. F. (2022). Influence of digital literacy on learning engagement among secondary students in Malaysia. Environment-Behaviour Proceedings Journal, 7(SI10). https://doi.org/10.21834/ebpj.v7isi10.4114 Simamora, N. N., Alrefay, K. A., Qasem, A. A., Lorenzo, A., & Kara, M. K. (2024). The influence of teachers’ digital literacy and the use of technology media on students’ ability to identify hoaxes in the digital era. Journal of Educational Technology and Learning Creativity, 2(2). https://doi.org/10.37251/jetlc.v2i2.1412 Soufghalem, A. (2024). The role of technology in enhancing digital literacy skills among secondary school students. International Journal of Post Axial: Futuristic Teaching and Learning. https://doi.org/10.59944/postaxial.v2i4.390 Tung, K. Y. (2025). Effects of digital learning platforms on academic achievement among secondary school students: A mixed-methods analysis. Journal of Hunan University Natural Sciences. https://doi.org/10.55463/issn.1674-2974.52.6.8 Yang, H., & Zheng, F. (2025). Investigating information literacy levels among primary and secondary school students: A survey-based study. American Journal of Education and Learning. https://doi.org/10.55284/ajel.v10i1.1457 Yıldırım, T., & Öztürk, D. (2023). A mixed-method research on digital literacy of middle school students. International Journal of Education and Literacy Studies. Zeren, E. (2023). Predicting secondary school students’ 21st-century skills through their digital literacy and problem-solving skills. International Education Studies, 16(2), 61–. https://doi.org/10.5539/ies.v16n2p61